Evaluate the performance of the Heads of Maintenance Department at Ministry of awqaf & Islamic affairs in the mosques of Qatar in the Light of Total Quality Management - Salem, Mamoun Youssef (Journal of Economic, Administrative and Legal Sciences, 2019)
This Research Paper aims to evaluate the Performance of the Heads of Maintenance Department of the Ministry of Awqaf and Islamic Affairs in the mosques of Qatar in light of the Total Quality Management (TQM) principals. To achieve this goal, the researcher conducted a field study consisting of a questionnaire containing 32 questions. The study targeted a random sample of 263 individuals (Stake Holders) in three grand mosques at different praying times and locations to measure their understanding about the role of the Maintenance Department and its employees, and the extent of involvement, as mosque users, in the process of decision-making. In addition, the level of their knowledge about the maintenance work was also studied. After analyzing the data, the most important results have been concluded; That There is a strong relationship between continuous evaluation and good performance of the Heads of Maintenance, and the External users are very important in improving and evaluation performance process.Finally, the most important recommendations is that the Heads of Maintenance should implement in all areas and at all levels TQM in order to reach a good standard of performance, and to adopting ambitious programs to increase the interaction and awareness of the internal and external users and to establish solid understanding about mosques maintenance among the users.
Keywords: performance appraisal; heads of maintenance departments; total quality management; mosques